ADSORPTION OF Mg(lI) AND Ca(lI) ON DISULFONATO-SILICA HYBRID - Azmiyawati, Choiril; Nuryono, Nuryono; Narsito, Narsito ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Adsorption of Mg(lI) and Ca(lI) on disulfonato-silicahybrid (DSSH) in the aqueous solution has been studied. The hybrid was synthesized by sol-gel process with sodium silicate solution from rice hull ash, chloroprophyltrimethoxysilane (CTS) and 4-amino-5-hydroxy-naphtalene-2, 7-disulfonic acid monosodium salt (ANSNa) as silica source, cross linker and active group, respectively. Sodium silicate solution was reacted with CTS and ANSNa that were added dropwise. Adsorption of magnesium and calcium ions on DSSH was carried out in a batch system. Solution pH significantly affected magnesium and calcium adsorption and the optimum condition was ootained at pH = 6. Thesynthesized DSSH showed a high adsorption capacity of 0.0844 mmol/g and 0.1442 mmol/g for Mg(lI) and Ca(II), respectively. The adsorption isotherm obtained with Langmuir isotherm model gives the negative values of . &#916